Evaluating the Potential for Solar Energy Utilization on Rooftop Surfaces - ALI Nurhalim Dani; BAHRI Syaiful; ROSMA Iswadi Hasyim; SIREGAR Yusni Ikhwan; SAAM Zulfan (Journal of Electrical and Electronics Engineering)
This research aims to design and evaluate a grid-connected solar rooftop photovoltaic system for an academic campus, specifically for implementation in the Electrical Engineering Laboratory Building of the Faculty of Engineering at the University of Riau. The design and feasibility study of this solar rooftop photovoltaic system project is based on meteorological data from the project area. This data was measured using an AWS (Automatic Weather Station) installed on the roof of the Electrical Engineering Laboratory Building of the Faculty of Engineering. The system's performance was simulated using PVsyst software, and the results were analyzed. All components were selected based on those available in the software used. A total of 656 solar panels are required. Theoretically, the rooftop PV system can generate 229,600 Wp. The energy generated by the PV array is 258,266 kWh/year, and the energy delivered to the grid is 250,709 kWh/year. The specific energy generated is approximately 1,090 kWh/kWp/year. This system has a relatively high performance ratio of around 82%. The system is highly capable of substituting the electricity energy needs of the Electrical Engineering Laboratory Building of the Faculty of Engineering at the University of Riau.